2012
DOI: 10.1177/0883073812443005
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic Drugs and Bone Metabolism in Children

Abstract: There are conflicting results concerning bone metabolism in children receiving antiepileptic medication, with data concentrating on neurologically impaired patients. We performed a multicenter cross-sectional study in otherwise healthy children who received monotherapy with valproic acid, oxcarbazepine, lamotrigine, sulthiame, levetiracetam, or topiramate for at least 6 months. Data on calcium, phosphorus, alkaline phosphatase, 25-OH vitamin D, and parathormone were collected. Among 128 patients, 24.4% had hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 28 publications
2
39
0
6
Order By: Relevance
“…17,34,36,38,39 These latter studies found this to be the case for non-enzyme-inducing anticonvulsants (valproic acid) use 36,38 or new anticonvulsants (lamotrigine, topiramate, oxcarbazepine, sulthiamine). 17,39 In this study, none of the subjects had vitamin D deficiency, but we found higher prevalence of vitamin D insufficiency in epileptic children (39%) compared to control subjects (13%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17,34,36,38,39 These latter studies found this to be the case for non-enzyme-inducing anticonvulsants (valproic acid) use 36,38 or new anticonvulsants (lamotrigine, topiramate, oxcarbazepine, sulthiamine). 17,39 In this study, none of the subjects had vitamin D deficiency, but we found higher prevalence of vitamin D insufficiency in epileptic children (39%) compared to control subjects (13%).…”
Section: Discussionmentioning
confidence: 99%
“…25,29,31,41 Third, most of our subjects consumed valproic acid which has less impact on reducing vitamin D levels than enzymeinducing anticonvulsants. 25,32,38 Several studies have shown that valproic acid was not associated with vitamin D deficiency. 36,38 Mean daily intake of vitamin D in our study was lower than that recommended by the Institute of Medicine (IOM).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in a recent study, BMD in pediatric epileptic patients has been found to be decreased by 9%. In particular, 5 patients, all boys, showed levels, although the patients under lamotrigine treatment had normal levels of calcium [20]. Additionally, a study by Lee et al found that lamotrigine treatment didn't affect BMD, vitamin D or calcium levels [5].…”
Section: Aeds and Bmdmentioning
confidence: 98%
“…Topiramate, a newer antiepileptic drug, has been associated with decreased levels of BMD [3,13], osteoporosis, hypocalcemia and increased bone turnover [5]. Finally, treatment with sulthiame, a carbonic anhydrase inhibitor, is associated with reduced calcium levels [20].…”
Section: Aeds and Bmdmentioning
confidence: 99%